'It proves falsehood absolutely . . .' The lost notebook of Dr. Frederick A. Cook. (24th January 2014) - Bryce, Robert M.
ABSTRACT: With the completion of a careful study of a photographic copy of the original notebook Frederick Cook kept on his attempt to reach the North Pole in 1908, now in Copenhagen, Denmark, many new details have been added that allow a more accurate account of his actual movements and timetable than has been possible previously. Because some records were altered or destroyed by Cook, however, a complete account still necessarily contains an element of speculation, which must be the case when based on the only records that exist of an unwitnessed assertion. But this uncertainty can be controlled to a reasonable degree by the notebook's remaining content in concert with the several other accounts Cook wrote of his expedition. One thing is sure, however: Cook was far behind his published timetable. At the outset, he set his start date back by one full week. He failed to report a number of delays in his journey and left out a lengthy detour that prevented him from reaching land's end at Cape Thomas Hubbard until well past 1 April 1908. This ruled out any chance to reach the North Pole in 1908. Frederick Cook was no fool; he was a veteran explorer. He knew any attempt that late in the season would be suicide. Furthermore his efforts to lay caches that would separate his own return route from that of his Inuit support party indicate that not only had he already given up the idea of making a serious attempt, but also that he was preparing for his eventual hoax of claiming to have reached the North Pole on 21 April 1908 long before he reached the Arctic Ocean.